After sundown : a novel - Howard, Linda, 1950-; Jones, Linda, 1954- (New York : William Morrow, 2020)
Sela Gordon, shy owner of a Tennessee general store, prefers solitude. If anyone can chip away at her protective shell it's the handsome, mysterious, ex-military man who's been hiding for two years in the wilds of Cove Mountain. But when he warns her that a catastrophic solar storm with the capability of taking down the power grids is approaching, Sela must come out of her shell and be the leader Wears Valley needs.
Keywords: General stores -- Fiction; Veterans -- Fiction; Man-woman relationships -- Fiction; Tennessee -- Fiction; Romance fiction; Thrillers (Fiction)